Rust resistance of wheat and triticale samples in different plant growing stages - G. V. Volkova; O. A. Kudinova; O. O. Ignatieva; V. D. Agapova; E. V. Gladkova; O. F. Vaganova; I. P. Matveeva (Юг России: экология, развитие, 2024)
Aim. To study resistance to leaf, yellow and stem rusts of winter and spring wheat and winter triticale samples from the collection of the N. I. Vavilov All‐Russian Institute of Plant Genetic Resources (VIR) and breeding centres of southern Russia in different phases of ontogenesis and to identify new sources with group resistance.   Material and Methods. The resistance of 158 wheat and triticale samples from the VIR collection and southern breeding centres to populations of leaf, stem and yellow rusts in different plant growth stages was analysed. In the juvenile phase the samples studied were inoculated with populations of rust fungi in climate chambers of the Federal Research Centre of Biological Plant Protection and the type of plant reaction to lesions was noted. In field conditions the samples were evaluated according to the CIMMYT scale on an artificial infectious background.   Results. In the adult plant stage under field conditions 79 wheat and triticale samples with group resistance to leaf, yellow and stem rusts were identified, and in the juvenile stage 26 samples. 22 samples showed resistance to three rusts in both phases of ontogenesis. Of these, 5 samples belong to the VIR collection, 3 winter triticale varieties (Dozor, Knyaz, Svat) and the Kavalerka wheat variety selection of the P.P. Lukyanenko National Grain Centre, 9 lines from the Donskoy Agrarian Research Centre and the Federal Rostov Agrarian Research Centre, and 4 winter triticale varieties (Ataman Platov, Zimogor, Kapral, Legion) of selections of the Federal Rostov Agrarian Research Centre.   Conclusion. The samples of wheat and winter triticale with group resistance which have been identified are promising for use in breeding for immunity to rust diseases.